2021
DOI: 10.1097/md.0000000000023175
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hydrogen peroxide-assisted endoscopic ultrasonography-guided necrosectomy in walled-off pancreatic necrosis

Abstract: Hydrogen peroxide is a liquid that functions in mechanical removal of the necrotic tissue via the elimination of tissue debris. In this study, we aimed to evaluate the effectiveness of the use of hydrogen peroxide in necrosectomy treatment of walled-off pancreatic necrosis. Records of 24 patients who were diagnosed with pancreatic necrosis or walled-off pancreatic necrosis and underwent endoscopic necrosectomy (EN) were retrospectively assessed. Patients were divided into 2 groups; hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Irrigation may facilitate the washout of infectious components within the cavity and accelerate PFC resolution. However, the study results have been inconsistent in terms of its effectiveness, 36,[47][48][49][50][51][52] and bacteremia may be provoked via the advertently increased intracystic pressure. Therefore, the starting time of irrigation should be determined with caution.…”
Section: Goal Of Endoscopic and Other Interventionsmentioning
confidence: 97%
“…Irrigation may facilitate the washout of infectious components within the cavity and accelerate PFC resolution. However, the study results have been inconsistent in terms of its effectiveness, 36,[47][48][49][50][51][52] and bacteremia may be provoked via the advertently increased intracystic pressure. Therefore, the starting time of irrigation should be determined with caution.…”
Section: Goal Of Endoscopic and Other Interventionsmentioning
confidence: 97%
“…In several previous studies, hydrogen peroxide has proven effective and safe in reducing debridements, even making external irrigation unnecessary in selected IPN patients[ 82 , 94 ]. Hydrogen peroxide has the advantage of healing INP by stimulating granulation and fibrosis, and foams produced by hydrogen peroxide in contact with organic tissue help remove the attached necrotic debris[ 95 ]. However, its operation time and treatment course to achieve equal clinical efficacy with routine debridement seem prolonged[ 96 ], and this technique's optimal procedure and concentration remain to be further studied[ 94 ].…”
Section: Endoscopic Transluminal Necrosectomymentioning
confidence: 99%
“…Hydrogen peroxide (H 2 O 2 ) is a colorless which rapidly dissociates into oxygen and H 2 O when in contact with organic tissues, producing a soft foam that helps removing materials attached to the tissue, including necrotic debris [70,71]. Furthermore, it seems help wounds healing by stimulating granulation and fibrosis [72]. In order to use its healing and chemical debridement properties, it has often been used as aid in DEN, despite lack of properly designed clinical trials to assess its efficacy, AEs, and technical aspects in such field [62].…”
Section: Irrigationmentioning
confidence: 99%
“…For this reasons, current international guidelines suggest restraint regarding H 2 O 2assisted DEN [13,14]. Many series and comparative trials, published both prior to and after the publication of the guidelines, reported a high technical and clinical success of H 2 O 2assisted DEN, a reduced number and duration of DEN sessions, with sometimes no need at all for mechanical debridement, and an AEs profile and rate similar to non-H 2 O 2 -assisted DEN [70,[72][73][74].…”
Section: Irrigationmentioning
confidence: 99%
See 1 more Smart Citation